225 OLDER PERSONS REHAB AT HOME (OPRAH) INDICATES AN EFFECTIVE ALTERNATIVE PATHWAY TO INPATIENT REHABILITATION. (25th October 2022) - Coen, M; Murphy, R; Connolly, A; O'Connor, A; Doyle, E; Byrne, S; Carty, J; Breen, C; Canavan, M; Waters, R; Robinson, S
Abstract: Background: Older adults have longer hospital stays, higher incidence of nosocomial complications and higher readmissions rates. Older persons rehabilitation at home (OPRaH) is a novel service developed to provide patients with intensive domiciliary based therapy to regain function, mobility and social care goals. OPRaH offers a comprehensive geriatric and interdisciplinary approach. The model enables a safe and accelerated discharge from acute care to home. Methods: Patients are identified and screened by a team coordinator. On Discharge to OPRaH the following measures were collected; basic demographics, referral source, clinical frailty score and Functional Independence Measures (FIM). Outcomes evaluated are the FIM change, readmission rates, length of inpatient stay savings and time on the service. Data from the first year of operation was analysed using descriptive statistics. Results: 109 patients have undergone rehabilitation with the service with a median age of 82 years (63-103 range). Over two thirds (68%) were classified as frail, with 44% living alone. An injurious fall was the most common reason for index hospitalisation (50%). Referral source was inpatient acute medical team in 50% of cases, with 21% from acute geriatrics, 13 % ortho geriatrics, 13% surgical. Average functional independence measure scores improved from 89 to 102 (p = 0.007). There was no difference in the magnitude of improvement by frailty status (13 vs 14, p = 0.85). The average length of stay saving was 7 days per case, with a total of 757 days saved in one year. Readmission rate within 30 days was 9.3 %. Participants highly rated the service through structured evaluation. Conclusion: This novel service provides a valuable intervention to a wide case-mix of older adults with evidence of improvements in formal markers of functional impairment after intervention. Referral was based on definable rehabilitation goals and not just on frailty status, age, or gender.